Potensi Pemanfaatan Ekstrak Etanol Alga Merah (Kappaphycus alvarezii) sebagai Pengawet Alami Pengganti Formalin pada Daging Ikan [Potential Use Of Red Algae Ethanol Extract (Kappaphycus alvarezii) As Formalin Substitute Natural Preservative In Meat Fish] - Wahju Tjahyaningsih; Muhammad Amin Alamsjah; Annur Ahadi Abdillah (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract Fish meat is more nutritious source of protein and relatively safe for human consumption. Fish meat more easily damaged than red meat product quality, so it is necessary that the process of pickling fish maintained in fresh condition and suitable for consumption. The ethanol extract of red algae Kappaphycus alvarezii been known have antioxidant and antimicrobial effects, so need some research on the use of red algae extract as a preservative. Red algae extract with a concentration of 400 ppm, 500 ppm, 600 ppm and 1 % formalin, each sample is used as a meat preservative for tilapia fillets as 40 grams. Samples of tilapia meat is soaked in an preservative solution as long as 60 minutes. During immersion, the samples of tilapia meat stored at room temperature. Observation of tilapia meat quality is done about six hours after meat removed from the preservative solution. Fish meat quality were analyzed to describe the organoleptic quality, methods of the TPC, and proximate analysis. The results showed that the ethanol extract of red algae Kappaphycus alvarezii 600 ppm has potential as a natural preservative based on test results of TPC, proximate and organoleptic test.